An Analysis of the Project Incubation Model of Self-Produced TV Dramas in the New Media Era - Zhao, Xiaoxuan (Journal of Intelligent Communication, 2022)
With the advent of the information age, the application of digital technology on the Internet has become more and more popular. Mobile phones, the Internet and other emerging media have brought a drastic impact on the traditional media era, and the status of traditional media is slowly weakening. Nowadays, new media devices and video websites are gradually becoming active in people’s lives, and the increasingly sophisticated digital means have led to the rapid rise of new media. Against this backdrop, traditional media are being squeezed to a great extent. In addition to being dominated by new media in terms of communication channels, the voice of traditional media in the market is also threatened to a certain extent. In addition to the problems of the traditional media themselves, and the lagging nature of the traditional media that is not in tune with the development of the times, the traditional media industry, especially the TV side and TV people, are gradually facing more pressure. Under pressure, there must be innovation. How traditional TV media can change and innovate requires us to rise to the occasion and be fully prepared for the current environment, and self-produced dramas are one of the paths that TV stations need to explore.